Decoding the Triglyceride/HDL-C Ratio: A Marker for Type-2 Diabetes Risk (GAIMS Journal of Medical Sciences, 2025)
Background: Diabetes mellitus (DM) is the most common endocrine disorder worldwide. Beyond the established markers of glycemic control and insulin resistance (IR), there remains a need for reliable, accessible, and reproducible indicators. To address this, our study evaluated the triglyceride to HDL cholesterol ratio (THR) as a potential marker for insulin resistance and glycemic regulation.Materials and methods: We retrospectively analyzed TG, fasting serum glucose (FSG), and fasting insulin levels from 953 samples processed between March and August 2024. Based on homeostasis model assessment-estimated insulin resistance (HOMA-IR) values, patients were categorized into two groups: good versus poor glycemic control. The discriminatory power of the triglyceride-to-HDL cholesterol ratio (THR) for differentiating these groups was evaluated using Receiver operating characteristic (ROC) analysis, with statistical significance set at p